1998
DOI: 10.1063/1.476790
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy and ab initio quantum chemical study of the Ã(1A″)−X̃(1A′) transition of CFBr

Abstract: The Ã(1A″)−X̃(1A′) electronic transition of jet-cooled CFBr has been investigated by spectroscopic and ab initio theoretical methods. Laser induced fluorescence (LIF) excitation spectroscopy was used to explore the rovibronic levels in the à state, and dispersed fluorescence spectroscopy was used to study ground-state vibrations. Analysis of these spectra yielded gas-phase vibrational frequencies and anharmonicity constants in both electronic states. The computed ab initio vibrational frequencies in both X̃ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
63
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(83 citation statements)
references
References 33 publications
19
63
1
Order By: Relevance
“…It has been indicated that the dissociation barrier height of the A-state of different carbenes follows a trend of CFCl > CFBr > CFI. 11,12,17,24 The barrier height of CFCl was experimentally determined to be 4073 cm −1 , 12 which was about 1700 cm −1 smaller than the result calculated at the CASPT2(18,12)/cc- 11 For CFBr, the latest LIF spectroscopic study 17 with sub-Doppler resolution gave a barrier height of about 1000 cm −1 , more than 2300 cm −1 smaller than the result from the early LIF and photofragment excitation spectrum, 24 which was attributed to the reassigned T 00 value of the Ã1A″ state. The newest experimental T 00 value 17 of CFBr (Ã1A″) was verified by recent high-level MRCI 18,20 and CASPT2 22 calculations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that the dissociation barrier height of the A-state of different carbenes follows a trend of CFCl > CFBr > CFI. 11,12,17,24 The barrier height of CFCl was experimentally determined to be 4073 cm −1 , 12 which was about 1700 cm −1 smaller than the result calculated at the CASPT2(18,12)/cc- 11 For CFBr, the latest LIF spectroscopic study 17 with sub-Doppler resolution gave a barrier height of about 1000 cm −1 , more than 2300 cm −1 smaller than the result from the early LIF and photofragment excitation spectrum, 24 which was attributed to the reassigned T 00 value of the Ã1A″ state. The newest experimental T 00 value 17 of CFBr (Ã1A″) was verified by recent high-level MRCI 18,20 and CASPT2 22 calculations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Such conclusion was deduced with the aid of comparing the calculated result of CFBr at the same theoretical levels with the experimental barrier reported by Knepp et al 24 Since no experimental results of the Ã1A″ state of CFI is available to compare with the calculation results, further study of the PES at higher levels of theory should be carried out. In fact, in the case of CFBr, Knepp's experimental results 24 were debated by Truscott et al 17 in their recent high-resolution LIF spectroscopic study, which reassigned the T 00 value of the Ã1A″ state to 23271 cm −1 (2365 cm −1 higher than Knepp's result 24 and is consistent with several following theoretical studies 18,20,22 ) and estimated the barrier height about 1000 cm −1 from fluorescence quantum yields (in contrast to Knepp's result of 3360 cm −124 ). In addition, a recent study 22 has demonstrated that the scalar relativistic effect, spin−orbit coupling (SOC), and core− valence (CV) effect should be considered in the calculation to obtain reliable energies of CFBr, which has not been investigated in CFI carbene.…”
Section: ■ Introductionmentioning
confidence: 89%
“…In previous work carried out in our group, a range of halocarbenes were studied, namely CF2 [14,191, HCF [13], HCCl [20], CFCl [20], CFBr [12], CC12 [14] and CBr2 [14], where the geometries, force constants and vibrational frequencies of the (singlet excited) A" states as well as the (ground) and (triplet) ii states were computed. The methods utilized in the characterization of the A state were primarily the complete active space self-consistent field (CASSCF) method [21,22] as well as multireference configuration interaction (MRCI) [23,24] and complete active space second-order perturbation (CASPT2) methods [25,261.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The lifetimes of HCF ( 22 have calculated CCl 2 excitation energies, equilibrium geometries, and vibrational frequencies of the seven lowest electronic states. They have also estimated oscillator strengths for dipole-allowed transitions from the ground electronic state.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable information is now available on the electronic transition to the first excited electronic state ( 1 B 1 ) of a number of halocarbenes, and vibrational energies and rotational constants in both ground and excited electronic states have been determined. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This has allowed determination of molecular geometries and information on the relevant potential energy surfaces. The 1 A 1 and 1 B 1 states coalesce to a degenerate electronic state at linear geometry, thus leading to the Renner-Teller effect which couples the two states.…”
Section: Introductionmentioning
confidence: 99%